Hydrocortisone, Vitamin C and thiamine for the treatment of sepsis and septic shock following cardiac surgery - Mahesh Balakrishnan; Hemang Gandhi; Komal Shah; Himani Pandya; Ramesh Patel; Sunny Keshwani; Nikhil Yadav (Indian Journal of Anaesthesia, 2018)
Background and Aims: The effect of vitamin C on vasopressor requirement in critically ill patients have been evaluated previously. We aimed to evaluate the effect of vitamin C, hydrocortisone and thiamine on vasopressor requirement and mortality in post-operative adult cardiac surgical patients with septic shock. Methods: About 24 patients with septic shock were randomised into Group 1 (receiving matching placebo per day for 4 days) and Group 2 (receiving 6 g vitamin C, 400 mg thiamine and 200 mg hydrocortisone per day for 4 days). Vasopressor dose over 4 days of therapy was the primary endpoint, whereas in-hospital mortality was the secondary endpoint. Results: APACHE IV and EUROSCORE II scores were similar between both the groups. Significant reductions in the requirement of vasopressin (difference from day 1 – 0.0008 ± 0.00289 vs 0.0033 ± 0.00492 units/kg/min; P = 0.019) and noradrenaline (difference from day 1 – 0.0283 ± 0.040 vs 0.023 ± 0.035 μg/kg/min; P = 0.006) were observed with vitamin C treatment as compared to control group. PCT levels on Day 3 (68.11 ± 33.64 vs 33.2 ± 27.55 ng/mL; P = 0.0161) and Day 4 (70.03 ± 29.74 vs 26.3 ± 23.08 ng/mL; P = 0.0009) were significantly lower in treatment group as compared to control. However, there was no difference in the Sepsis-Related Organ Failure Assessment (SOFA) score and mortality between the studied groups. Conclusion: Combination of vitamin C, thiamine and hydrocortisone reduces vasopressor requirement in adult cardiac surgical patients with septic shock.